PERAN ULAMA KALANGAN NAHDLATUL ULAMA (NU) DALAM KONTESTASI PEMILIHAN BUPATI DI KABUPATEN PURBALINGGA TAHUN 2020 - Cahyani, Amalia Sukma; -, supratiwi - (Journal of Politic and Government Studies, 2024)
This research aims to determine the role and factors that made Ulama from the Nahdlatul Ulama circle play a role in the contestation for the Purbalingga Regency Regent Election in 2020. By using the thory of political behavior by Ramlan Surbakti and Elite Theory bya Pareto and Putnam, the research that the author conducted was descritive qualitative research by obtaining data and information in accordance with what was in the field. The research results show that the role of Ulama from the Nahdlatul Ulama group in the Regent Election in Purbalingga Regency in 2020 was as a figure who became a reference for this knowledge and became a reference in determining political attitudes. The background of Ulama Nahdlatul Ulama to participate in the Regent Election process in Purbalingga is mainly religious factors and the mutual need for relegion and politics